Effect of temperature and scarification over the germination of Ischaemum rugosum Salisb. - Portuguez-García, Mary Pamela (2020)
Introduction. The rupture of the Ischaemum rugosum Salisb. latency is a critical aspect of its physiology, so its knowledge is indispensable to establish accurate measurements regarding its management. Objective. Determine if storage temperature and scarification influence the germination of I. rugosum under controlled conditions. Materials and methods. The work was carried out in October 2015 at the Fabio Baudrit Moreno Experimental Station and the Official Seed Quality Analysis Laboratory, both at the Universidad de Costa Rica. The effect of scarification (seeds with glumes and seeds without glumes), the seed storage temperature (refrigerated at 5 ¡C and environment temperature 23.9 °C), and the germination chamber temperature (27 °C and 30 °C) were evaluated. Germinated seeds were counted for each treatment. Results. Double interactions were significant. Seed stored at room temperature had the advantage of higher germination than non-scarified seed (2.35 to 1), and in this type of seed occurs equally in the two temperatures of the germination chamber. In relation to the seed stored in refrigeration, scarified seed had an advantage of germinating at 11.9 to 1 over the non-scarified seed. In the case of germination temperature, 27 °C had an advantage of 11.3 to 1 over 30 °C. Conclusion. The storage and germination temperature had an influence on the scarified and non-scarified seed’s germination.